Dynamics of Policy Network in the Development of Rainbow Village in Semarang City - Bariklana, Muhammad Nuqlir (Jurnal Administrasi Publik (Public Administration Journal), 2024)
This article aims to analyze the problems of the Rainbow Village in Semarang City. The success of the Rainbow Village at the beginning of its development contrasts with the current conditions that are empty of visitors, damaged paint conditions, and many wild plants growing along the road between people's houses. The problem analysis will focus on studying policy networks in implementing Kampung Pelangi. The existence of policy networks in implementation and policy-making is interesting to examine because the process involves a political process that is not only controlled by the state but involves various actors and diverse interests. Through qualitative methods and the theoretical framework of Waarden and Rhodes' policy networks, this paper wants to answer how the dynamics of policy networks run and the types of policy networks that develop. As a result of the study, the Rainbow Village policy network tends to be unstable and only runs when this program goes viral in the early days of implementation. The network built involves three important policy stakeholders, namely civil society, the private sector, and the government. The interaction between actors in policy networks tends to be unbalanced so there are inequalities in the distribution of resources and authority. This causes pokdarwis as the leading actor of the network to have difficulty maintaining the network's existence. The type of policy network is an issue network, where the network is temporary when program issues arise and network actors are not bound in a permanent network.